(untitled) (Journal of International Crisis and Risk Communication Research, 2022)
Since the death of George Floyd in Minneapolis, at least 140 cities across the United States have experienced protests resulting in vandalism, looting, shootings, and other violence. These protests represent a challenge for community organizations such asconvention and visitors bureaus (CVBs), whose responsibility is to promote their local community as a place for tourism, meetings, conferences, and other activities. This study explores the response of Visit Aurora, a Colorado CVB to engage their local protestsinspired by the BLM movement, and a local case—the death of Elijah McClain. Within the paper a model for crisis engagement will be discussed, including the ethical responsibilities of institutions to support stakeholders even when they may not be directly responsible for the harms they have experienced.